Identification of evolutionarily conserved gene networks mediating neurodegenerative dementia. - Swarup, Vivek (Nat Med, 2018)
Identifying the mechanisms through which genetic risk causes dementia is an imperative for new therapeutic development. Here, we apply a multi-stage, systems biology approach to elucidate disease mechanisms in frontotemporal dementia (FTD). We identify two gene co-expression modules that are preserved in mice harboring mutations in MAPT, GRN, and other dementia mutations on diverse genetic backgrounds. We bridge the species divide via integration with proteomic and transcriptomic data from human brain to identify evolutionarily conserved, disease-relevant networks. We find that overexpression of miR-203, a hub of a putative regulatory miRNA module, re-capitulates mRNA co-expression patterns associated with disease state and induces neuronal cell death, establishing this miRNA as a regulator of neurodegeneration. Using a database of drug-mediated gene expression changes, we identify small molecules that can normalize the disease-associated modules and validate this experimentally. Our results highlight the utility of an integrative, cross-species, network approach to drug discovery.